2003
DOI: 10.1081/pfc-120025561
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Soil Environment in the Post‐Flooding Area: Content of Polycyclic Aromatic Hydrocarbons (PAHs) and S‐Triazine Herbicides

Abstract: Impacts of flooding on the soil environment with regard to soil pollution with polycyclic aromatic hydrocarbons and s-triazine (cyanazine, simazine, atriazine, propazine, prometryn) herbicides have been evaluated. No clear differences in the sum of the PAHs content were observed in the present studies. Only changes in the levels of individual PAHs were noted. In soils covered with flooding both at a depth of 0-20 and 20-40 high molecular weight PAHs were predominant (especially mutagenic and carcinogenic 5-rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…[1] Hence, it has become necessary to continuously monitoring their content, mainly in those elements of the natural environment directly related to human life (food, water, etc.). [2,3] There are a number of different pathways by which POPs may enter vegetation. These include uptake by roots and subsequent translocation in the xylem, volatilization from the soil followed directly by foliar uptake from the gaseous phase or directly from the surrounding atmosphere via wet or dry deposition.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Hence, it has become necessary to continuously monitoring their content, mainly in those elements of the natural environment directly related to human life (food, water, etc.). [2,3] There are a number of different pathways by which POPs may enter vegetation. These include uptake by roots and subsequent translocation in the xylem, volatilization from the soil followed directly by foliar uptake from the gaseous phase or directly from the surrounding atmosphere via wet or dry deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been determined (Jones et al 1989;Tebaay, Welp, and Bremmer 1993;Cousins, Gevao, and Jones 1999) that PAHs are accumulated mainly in the 0-to 10-cm soil horizon. However, studies showed that PAH transportation into the depths of the soil profile is possible (Jones et al 1989;Tebaay, Welp, and Bremmer 1993;Cousins, Gevao, and Jones 1999;Baran, Oleszczuk, and Baranowska 2003). Surfactants (Loser et al 2000), dissolved organic carbon (Raber and Kögel-Knabner 1997;Marschner 1998), soil colloids (McCarthy andZachara 1989), and some microorganisms and invertebrates (Jenkins and Lion 1993;Belfroid, Sijm, and van Gestel 1996) can exert influence on solubility and desorption of PAHs.…”
Section: Concentration Of Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 97%
“…Herbicide members of this family include atrazine, hexazinone, metribuzin, prometon, prometryn, and simazine. Atrazine is one of the most used herbicides in Europe and the USA [48]. These compounds are known to have a moderate toxicity; yet can undergo transformation to more toxic, mutagenic, and carcinogenic forms.…”
Section: Triazine Pesticidesmentioning
confidence: 99%